Relation between academic achievement motivation and academic achievement in secondary students from a private and public school in Lima - Thornberry-Noriega, Gaby (2003)
The Academic Achievement Motivation (AAM) test was created for Peruvian secondary students. The AAM was applied to a sample of 166 students. It was found that their school and gender does not influence the degree of correlation between the AAM and the final grades of the students. It was found though, that the level of AAM obtained by the students is affected by the type of school but not by their gender. The level of their AMM, on the other hand, was influenced by the type of school and by their gender. A qualitative analysis showed that students from the public school had higher academic achievement motivation than students from the private school. In addition, the analysis showed that students from the private school obtained higher grades than students from the public school.